Engineering a functional thyroid as a potential therapeutic substitute for hypothyroidism treatment: A systematic review - Li, Lei; Sheng, Qixuan; Zeng, Huajin; Li, Wei; Wang, Qiang; Ma, Guanjun; Qiu, Ming; Zhang, Wei; Shan, Chengxiang (Frontiers in Endocrinology, 2022)
Background: Hypothyroidism is a common hormone deficiency disorder. Although hormone supplemental therapy can be easily performed by daily levothyroxine administration, a proportion of patients suffer from persisting complaints due to unbalanced hormone levels, leaving room for new therapeutic strategies, such as tissue engineering and regenerative medicine. Methods: Electronic searches of databases for studies of thyroid regeneration or thyroid organoids were performed. A systematic review including both in vitro and in vivo models of thyroid regenerative medicine was conducted. Results: Sixty-six independent studies published between 1959 and May 1st, 2022 were included in the current systematic review. Among these 66 studies, the most commonly involved species was human (19 studies), followed by mouse (18 studies), swine (14 studies), rat (13 studies), calf/bovine (4 studies), sheep/lamb (4 studies) and chick (1 study). In addition, in these experiments, the most frequently utilized tissue source was adult thyroid tissue (46 studies), followed by embryonic stem cells (ESCs)/pluripotent stem cells (iPSCs) (10 studies), rat thyroid cell lines (7 studies), embryonic thyroid tissue (2 studies) and newborn or fetal thyroid tissue (2 studies). Sixty-three studies reported relevant thyroid follicular regeneration experiments in vitro, while 21 studies showed an in vivo experiment section that included transplanting engineered thyroid tissue into recipients. Together, 12 studies were carried out using 2D structures, while 50 studies constructed 3D structures. Conclusions: Each aspect of thyroid regenerative medicine was comprehensively described in this review. The recovery of optimal hormonal equilibrium by the transplantation of an engineered functional thyroid holds great therapeutic promise.